The Indochinese-Sundaic faunal transition at the Isthmus of Kra: An analysis of resident forest bird species distributions - Jennifer B. Hughes (2018)
Aim: To establish the geographical position of the biogeographical transition between Indochinese and Sundaic faunas using distributional data for the best-documented taxon, the birds. Methods: Distributional data of 544 resident forest and forest edge bird species of Thailand and the Thai-Malay peninsula were examined at 45 sites spanning 15° of latitude from northern-most Thailand to the southern peninsular Malaysia. Sites were grouped into 23 degree or half-degree latitudinal zones and avifaunal similarity coefficients were calculated between each zone. Results: A Mantel test revealed a significant transition between northern Indochinese and southern Sundaic (Indomalay) avifauna assemblages just north of the Isthmus of Kra (10°30′ N). Northern and southern range limits of 152 species (> 269 species and subspecies combined) lie between 11° and 13° N. Main conclusions: This transition between zoogeographical subregions is not coincident with the widely recognized transition between floristic provinces which is traditionally placed 400-500 km further south at the Kangar-Pattani line, but is associated with a change from wet seasonal evergreen dipterocarp rain forest to mixed moist deciduous forest north of the Isthmus of Kra in the northern Thai-Malay peninsula. Climatological and ecological factors associated with the distribution of forest types today are reviewed and it is hypothesized that the avian transition tracks the northern phytogeographical boundary. Palaeogeographical factors, including hypothetical Neogene seaways, which may account for the historical development of both phytogeographical and avifaunal transitions are also described.